Adult urological soft tissue sarcomas: A multicenter study of the anatolian society of medical oncology (ASMO) - Unal, Olcun Umit; Oztop, Ilhan; Menekse, Serkan; Urakci, Zuhat; Bozkurt, Oktay; Ozcelik, Melike; Benekli, Mustafa (Asian Pacific Organization for Cancer Prevention, 2015)
Objective: To analyze clinicopathological characteristics, prognostic factors and survival rates of the patients with urological soft tissue sarcomas treated and followed up in Turkey. Materials and Methods: For overall survival analyses the Kaplan-Meier method was used. From medical records, nine prognostic factors on overall survival were analysed. Results: For the 53 patients (34 males, 19 females) whose charts were reviewed, the median age was 53 (range 22 to 83) years. Most frequently renal location (n=30; 56.6%) was evident and leiomyosarcoma (n=20, 37.7%) was the most frequently encountered histological type. Median survival time of all patients was 40.3 (95% CI, 14.2-66.3) months. In univariate analysis, male gender, advanced age (=50 years), metastatic stage, unresectability, grade 3, renal location were determined as worse prognostic factors. In multivariate analysis, metastatic stage, unresectability and grade 3 were determined as indicators of worse prognosis. Conclusions: Urological soft tissue sarcomas are rarely seen tumours in adults. The most important factors in survival are surgical resection, stage of the tumour at onset, grade and location of the tumour, gender and age of the patients.
Keywords: Prognostic factors; Survival; Turkey; Urologic sarcoma